2012
DOI: 10.1590/s0100-29452012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação física, química e fitoquímica de frutos de Physalis, ao longo do período de colheita

Abstract: RESUMO-Physalis peruviana L. é uma espécie que vem sendo incorporada em plantios de pequenas frutas. Esta frutífera é tratada como anual, e o principal método de propagação é por sementes. Seu cultivo apresenta uma dinâmica de colheita diferenciada, com duração do período de colheita superior a três meses. Acredita-se que, devido ao extenso período de colheita, associado a diferentes épocas de semeadura, irão ocorrer variações nas características dos frutos. O objetivo deste trabalho foi avaliar as característ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
0
15
2
12
Order By: Relevance
“…The phenolic compounds contents found in fruits of P. peruviana were inferior to the ones reported by Lima et al (2012), who found variations between 150.04 and 210.04 mg EAG·100 g -1 ; however, these values were superior to the ones of Rockenbach et al (2008), between 57.9 and 47.8 mg EAG·100 g -1 of total phenolics in methanolic and aqueous extracts, respectively.…”
Section: Ss Contentcontrasting
confidence: 80%
See 1 more Smart Citation
“…The phenolic compounds contents found in fruits of P. peruviana were inferior to the ones reported by Lima et al (2012), who found variations between 150.04 and 210.04 mg EAG·100 g -1 ; however, these values were superior to the ones of Rockenbach et al (2008), between 57.9 and 47.8 mg EAG·100 g -1 of total phenolics in methanolic and aqueous extracts, respectively.…”
Section: Ss Contentcontrasting
confidence: 80%
“…Other values of antioxidant activity are cited for the species when evaluated by the method of kidnapping of the ATBS radical. Lima et al (2012) found antioxidant activity of 1.50 and 1.45% of kidnapping of the ABTS radical.…”
Section: Ss Contentmentioning
confidence: 93%
“…These values are higher than the conditions in greenhouse cultivation, as reported by Rodrigues et al (2013), in which a study under greenhouse conditions reached a production of 215 g plant -1 . The treatment in which pruning was not carried out, presented the best productivity (6.97 t ha -1 ) in relation to plants that underwent pruning of productive stems; these values are among means found by Lima et al (2010) Lima et al (2012), whom investigated the evaluation of Physalis peruviana L. fruits quality throughout the harvesting season, when they found mean fruit mass values between 3.0 and 5.0 g. The highest means found in plants trained with two stems in relation to plants maintained with four stems might be associated with Physalis peruviana L. fruiting dynamics. This species has a long harvesting period and after peak production, a decrease in the number of fruits occur as a function of the change of source/sink relation (RUFATO et al, 2008), in which the practice of maintaining two stems may have possibly affected this relation.…”
Section: Resultsmentioning
confidence: 69%
“…Thus, the H° parameter was able to clearly demonstrate the changes in coloration, decreasing with the maturation advance and reaching values close to 90° at more mature stages (totally yellow and predominantly yellow), characterizing the yellow coloration. Lima et al (2012) reported values of the Hue angle between 75.17 and 78.39° in P. peruviana fruits whose sowing was carried out in September, and the seedlings transplanted in November; and between 73.12 and 78.23° (coloration between orange to intense orange, characteristic of the species) for those planted in November and transplanted in January. These values are lower than those found in this study for P. angulata (86.51) and P. pubescens (85.59), which revealed fruits tending to the yellow color as maturation advanced.…”
Section: Maturity Stagesmentioning
confidence: 99%